2018
DOI: 10.3390/coatings8020083
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Tribological Properties of Spark-Anodized Titanium by Magnetron Sputtered Diamond-Like Carbon

Abstract: Spark-anodization of titanium can produce adherent and wear-resistant TiO 2 film on the surface, but the spark-anodized titanium has lots of surface micro-pores, resulting in an unstable and high friction coefficient against many counterparts. In this study, the diamond-like carbon (DLC) was introduced into the micro-pores of spark-anodized titanium by the magnetron sputtering technique and a TiO 2 /DLC composite coating was fabricated. The microstructure and tribological properties of TiO 2 /DLC composite coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Chen et al, reported a two-step process of producing carbon incorporated PEO treated titanium oxide coatings with improved tribological behaviour. The authors used magnetron sputtering to deposit diamond-like carbon into the micropores of PEO-treated commercial grade-2 titanium metal 19 . Nitrogenation of TiO 2 -based ceramic coatings is another well-researched method for improving their functionality; however, there are no reports of incorporating nitride content into PEO-treated titanium alloys by modifying the electrolyte composition.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, reported a two-step process of producing carbon incorporated PEO treated titanium oxide coatings with improved tribological behaviour. The authors used magnetron sputtering to deposit diamond-like carbon into the micropores of PEO-treated commercial grade-2 titanium metal 19 . Nitrogenation of TiO 2 -based ceramic coatings is another well-researched method for improving their functionality; however, there are no reports of incorporating nitride content into PEO-treated titanium alloys by modifying the electrolyte composition.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, lots of experimental studies on the tribological properties of DLC films have been carried out by investigating the effects of intrinsic properties, i.e., hydrogen concentration, hardness, metal/nonmetal doping, and so on [8][9][10][11]. However, the tribological properties of DLC films depend on not only the intrinsic parameters, but also many extrinsic factors, such as sliding velocity, normal load, environment atmosphere, and properties of friction interfaces [12][13][14][15]. In particular, the effect of sliding velocity on the friction characteristics of DLC films has been extensively studied, giving rise to a large amount of diverging findings [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was in connection with the unique structure of PEO TiO 2 coating. The PEO coating typically has a rough and porous outer layer and a dense inner layer [13]. The porous outer layer featured with high surface roughness and varied internal microstructure, which contributed to the high and unstable friction coefficient at the initial stage of the test.…”
Section: Tribological Behaviorsmentioning
confidence: 99%
“…In the previous study, we have explored depositing diamond-like carbon (DLC) on the PEO coating by using the unbalanced magnetron sputtering technique. Although results show that the TiO 2 /DLC composite coating exhibits improved tribological properties with low friction coefficient and low wear rate, DLC coating deposition is an expensive and time-consuming process [13]. Furthermore, this technique is not favorable to producing coatings on complex-shaped specimens.…”
Section: Introductionmentioning
confidence: 99%